2010
DOI: 10.1111/j.1469-7610.2010.02209.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a classroom‐based psychosocial intervention in conflict‐affected Nepal: a cluster randomized controlled trial

Abstract: A school-based psychosocial intervention demonstrated moderate short-term beneficial effects for improving social-behavioral and resilience indicators among subgroups of children exposed to armed conflict. The intervention reduced psychological difficulties and aggression among boys, increased prosocial behavior among girls, and increased hope for older children. The intervention did not result in reduction of psychiatric symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
177
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 250 publications
(184 citation statements)
references
References 32 publications
(43 reference statements)
5
177
1
1
Order By: Relevance
“…Eight school interventions were developed in the implementing country. Five interventions were adapted versions of evidence-based interventions from high income countries [37,38,42,[47][48][49].…”
Section: School-based Programmesmentioning
confidence: 99%
“…Eight school interventions were developed in the implementing country. Five interventions were adapted versions of evidence-based interventions from high income countries [37,38,42,[47][48][49].…”
Section: School-based Programmesmentioning
confidence: 99%
“…Previous evaluation studies of psychosocial interventions in diverse settings have found differing effects by age and gender [17][18][19][20][21]. In addition, we were interested in the moderating roles of family-level variables, including household size, family connectedness, displacement status, and family composition.…”
Section: Introductionmentioning
confidence: 99%
“…Thus using diagnosis for inclusion or for measuring outcome, which might improve the interpretation of results in studies of children with psychiatric conditions, is not appropriate for these community-based studies. For example, studies of school-based interventions which have not found a decrease in psychiatric symptoms have found improvement on indicators of psychological difficulty, social behavior, well-being [19], and functioning [39]. Thus, future studies may be enhanced by including a greater range of outcomes beyond psychiatric symptoms.…”
Section: Clinically Significant and Meaningful Resultsmentioning
confidence: 96%
“…Of the five cluster randomized studies, two were randomized by classroom [14,32] and three were randomized by school [19,20,33]. See Table 1.…”
Section: Random Assignment and Type Of Controlmentioning
confidence: 99%
See 1 more Smart Citation